Retrospective review of maternal deaths and maternal near misses due to major obstetric haemorrhage at a tertiary care centre in India - Agrawal, Swati; Singh, Anuradha; Biswas, Ratna; Singh, Abha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal near miss (MNM) is now widely accepted as a better indicator of maternal health than maternal death and reflects the quality of obstetric care in a particular institution. Methods: This is a retrospective study conducted at Lady Hardinge Medical College and Smt. Sucheta Kriplani Hospital over a period of 12 months (April 2016-March 2017), of all cases of maternal death and near miss maternal deaths due to major obstetric haemorrhage(MOH). Results: During the period reviewed, there were 13,083 deliveries, 12,958 live births and 37 maternal deaths. There were 30 cases of near miss maternal deaths and 2 maternal mortalities due to MOH. The mortality index was 6.25%. Severe maternal outcome ratio (SMOR) was 2.46. Among the near miss cases (n=30), morbidly adherent placenta was the cause in 26.6% of cases(n=8), postpartum hemorrhage in 23% of cases(n=7); rupture uterus in 13% cases(n=4); massive abruption in 13% of cases(n=4) and placenta praevia with antepartum haemorrhage in 3% of cases(n=1). Early obstetric haemorrhage due to ruptured ectopic pregnancy and incomplete abortion resulted in MNM in 16% (n=5) and 3.3% (n=1) cases respectively. It was observed that in 40% (n=12) of MNM cases (8 cases of morbidly adherent placenta plus 4 cases of rupture uterus), previous cesarean section was the single most important causative factor for the morbidity of the patient. Conclusions: Reduction in cesarean section rates is imperative to reduce morbidity and mortality associated with MOH.